Predicting coke morphology in Delayed Coking from feed characteristics. (1st March 2020) - Ovalles, Cesar; Rogel, Estrella; Hajdu, Paul; Rea, Thomas; Chaudhuri, Kaustav; Hench, Kyle; Cuspard, Danielle; Moir, Michael E.
Abstract: Currently, there is no well-established methodology to predict coke morphology in Delayed Coking from feed characteristics. We found that for a series of fourteen coking feeds from different parts of the world, coke morphology and shot-coke propensity can be predicted by determining the asphaltene solubility parameter using the asphaltene solubility profile method without further separation and in ~25 min runs. The results are attributed to asphaltenes with higher solubility parameters that favor phase separation from the hydrocarbon matrix and lead to shot coke formation. Similarly, asphaltene peptizability measured by flocculation onset, ΔPS stability parameter determined by asphaltene solubility profile, and surface area measurements of MCRT cokes showed good potential for predicting coke morphology and shot-coke tendency of coking feeds. Conversely, mean particle size measured by cross-polarized light optical microscopy of the MCRT cokes showed a relatively large dispersion of the data and a weak correlation with the shot-coke propensity. Finally, a general scheme for the formation of shot and sponge cokes during Delayed Coking was proposed.